The Blood Carboxyhemoglobin Levels of Individuals Occupationally Exposed to Traffic Related Air Pollution - Güvendik, Gülin; Yılmaz, Ayşegül (The Bulletin of Legal Medicine, 2001)
The aim of this study was to determine the blood carboxyhemoglobin (COHb) levels of traffic policemen, taxi drivers and gas station employees who are exposed to traffic-related air pollution. Spectrophotometric method was used for the determination of carboxyhemoglobin saturation percent in blood samples. The mean COHb level of blood samples from traffic policemen was found to be 8.5 + 0.90 % for smokers (n=ll), 5.32±0.26 % for nonsmokers (n= 10). In taxi drivers , it was found to be 6.75±0.68% for smokers (n=13), 4.47±0.44% for nonsmokers (n = 7) and in gas station employees carboxyhemoglobin levels of smokers (n= 11) and nonsmokers (n = 9) were 7.12+0.58% and 5.51±0.30% respectively. Carboxyhemoglobin saturations in control group were 3.43+0.16% for smokers (n = 30) and 0.88±0.05% for nonsmokers (n = 20). According to the results of statistical evaluation, significant differences were found between COHb values of the control group and policemen, taxi drivers, gas station employees when compared separetely (p